The Manhattan Project and the atomic bomb in American history - Gonzales, Doreen (Berkeley Heights, NJ : Enslow Pub., 2000)
This book describes the events and people surrounding the creation of the atomic bomb, and examines the effects of its use during World War II.
Includes index.
Includes chronology.
Includes bibliography.
4-8
Accelerated Reader AR
Keywords: Manhattan Project (U.S.) -- History; Atomic bomb -- History